(untitled) (Journal of Pathology of Nepal, 2024)
Pancytopenia as a result of hemophagocytosis in a middle-aged man presenting with high-grade fever of unknown etiology could be a rare consequence of Histoplasmosis infection. In the past, many cases of patients with human immunodeficiency virus infection contracting histoplasmosis-induced hemophagocytosis have been well documented, however, little data has been entered in the setting of HIV non-reactive status. Interestingly, we report a case of histoplasmosis in an immunocompetent male with the presence of yeast forms of H. capsulatum in the bone marrow smears. The patient was subsequently placed on Amphotericin B and corticosteroids but lost to the infectious disease. Cases like this, highlight the importance of taking into account the early decision for bone marrow sampling with careful attention to microscopic details as incidental pathologies may be elicited which could have significant effects on patient’s prognosis.